Effect of different computer assisted instruction web site contents on swimming instruction of elementary school children - Sengoku, Y.; Ichikawa, H.; Nomura, T. (Biomechanics and Medicine in Swimming IX, 2003)
The purpose of this study was to develop a Computer Assisted Instruction (CAI) web site for an elementary school swimming class, and to assess the learning effect from different CAI contents. A BBS (Bulletin Board System, textual information) to which the children could contribute their questions freely and a multimedia contents (movie information) were made for the CAI web-contents. One elementary school (5th-6th grad,en=39) participated in this study over two years (2000-2001). A questionnaire was conducted to analyze the effect of the CAI web site. Comparing the results between BBS and multimedia utilization, children answering "Useful to have new findings on swimming" was significantly higher using multimedia contents (BBS: 19.2 %, multimedia: 61.5 % p < .01) and the "affective" component was significantly higher in BBS utilization from analyzing free written answer (BBS: 22.5 %, multimedia: 3.0% p < .05). From the present study, it was concluded that by using BBS children can enjoy learning swimming with other pupils and multimedia contents can give more information for discovering how to swim.